2019
DOI: 10.3126/ijasbt.v7i1.23312
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Age and Frequency of Collection on Quality of Jersey Bulls Semen at National Livestock Breeding Center (NLBC), Nepal

Abstract: Objective: To determine the effect of age and frequency of collection on quality parameters of Jersey bull semen at National Livestock Breeding Center (NLBC), Pokhara. Materials and Methodology: Nine Jersey bulls were selected randomly from NLBC. To obtain the effect of age, six bulls of three different age interval (3-4, 5-7 and 8-9 years) were selected randomly. Remaining three bulls were used to determine the effect of frequency of collection on semen quality. Studies were conducted for three months (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 6 publications
1
4
0
Order By: Relevance
“…In the present study, the volume of an ejaculate ranged from 1.5 to 8 mL with double collection technique. Generally, the volume of first ejaculate is higher than the following consecutive ones [21,29]. Similarly, in the current study, a decrease was observed in the volume of second ejaculate in overall and each breed group, especially in FM-0 group.…”
Section: Discussionsupporting
confidence: 82%
“…In the present study, the volume of an ejaculate ranged from 1.5 to 8 mL with double collection technique. Generally, the volume of first ejaculate is higher than the following consecutive ones [21,29]. Similarly, in the current study, a decrease was observed in the volume of second ejaculate in overall and each breed group, especially in FM-0 group.…”
Section: Discussionsupporting
confidence: 82%
“…Table 1 shows that, the volume of semen obtained was lower than that reported by some previous researchers, namely 5.48 to 6.44 ml (Bhave et al, 2022), 5.20 ± 0.08 ml with variation from 5.12 ± 0.15 to 5.98 ± 0.09 among the ages 3 -9 years (Sankhi et al, 2019), 4.84 ± 0.01 ml in Kankrej bulls semen (Patel and Siddiquee, 2013), and 10.5 ml (Hossain et al, 2012). This difference was presumably caused by the sexual break of Brangus bulls for several years, and poor quality of the woof.…”
Section: Resultsmentioning
confidence: 57%
“…In this process, post-thaw sperm concentration and production efficiency are evaluated according to the variables specified. Nevertheless, sperm characteristics such as semen volume, concentration, and pH may in a large variation specific to the breed, as well as they may vary depending on factors such as age, climate, number of false mounting and ejaculation frequency (Khawaskar et al, 2012;Murphy et al, 2018;Sankhi et al, 2019;Şahin et al, 2020).…”
Section: Discussionmentioning
confidence: 99%